Investigating “physical mediums” via audio signal processing: A comment on Eckhard Kruse’s approach - Nahm, Michael (Journal of Scientific Exploration, 2018)
Abstract – Technological advances of the last decades offer possibilities to study phenomena of physical mediumship using new approaches of investigation. Such an approach is represented by Eckhard Kruse’s analyses of supposed “spirit voices” recorded in dark séance rooms during sittings with an alleged physical medium, Warren Caylor. Kruse concluded that the results of his investigations provide evidence, if not proof, demonstrating that these voices are indeed produced by materialized “spirits”. He publicized this interpretation of his work via various dissemination channels. As I will show in this article, however, Kruse’s approach of studying these “spirit voices” is loaded with severe conceptual and methodological deficiencies that ultimately render his claims untenable.